Experimental and numerical analysis of the energy performance of building windows with solar NIR-driven plasmonic photothermal effects. (1st October 2021) - Zhang, Enhe; Duan, Qiuhua; Wang, Julian; Zhao, Yuan; Feng, Yanxiao
Highlights: Demonstrate a novel solar infrared energy utilization on building windows. Propose and validate an analytical model for windows with nano photothermal effects. Introduce an insulation induced by plasmonic photothermal effects at building scale. Incorporate plasmonic photothermal effects into parametric energy simulation. Establish a physics-based regression model for photothermal windows' SHGC. Abstract: Thin films made of metallic nanoparticles can exhibit strong photothermal effects (PPE) on near-infrared light irradiation, paving a way for new designs of spectrally selective building windows for solar infrared modulation that operates without the need to compensate for visible transmittance. More importantly, the surface plasmon-induced light-to-heat conversion creates strong localized heating effects with a much smaller fraction resulting in the heating of the substrate. Incorporating such nanoscale PPE into the design of complex building fenestrations, this research conducted a comprehensive analysis to better understand the PPE-induced heating effect and conductive, convective, and radiative heat exchanges between windowpane surfaces and the surrounding indoor and outdoor environments. The authors first developed and then validated a numerical analysis method to incorporate spectral features, solar spectral irradiance, and nanoscale PPE. Subsequently, using the established numerical method, two-dimensional windowpane temperature profiles and solar heat gains were yielded under different boundary conditions. To understand the energy performance of windows with solar near-infrared-dependent PPE, a series of parametric energy simulations was employed. The results show the photothermal coating can be used as a new energy-efficient retrofit technology for single-pane windows, with heating energy saving 16.2–20.8%, which performs similar to the double pane windows. Notably, these energy savings were not achieved by increasing the thermal insulation via additional layers or insulating materials, but rather by the spectrally selective design of glazing materials and utilization of solar near-infrared energy. This work presents the energy saving mechanism on an architectural scale due to the nanoscale surface plasmon-induced photothermal effect and associated heat gain coefficient enhancement. It also poses a fundamental reference for the future integration of this novel nanoscale phenomenon into the building envelope systems.